The Determinants of Executive Pay and its Role in Corporate Governance - HUANG, JIAQI (2018)
Executive compensation is an important part that cannot be ignored in corporate management. This article aims to provide some new evidence for existing research. According to the executive compensation of 50 listed companies from different industries in the UK between 2011 and 2015, the determinants of executive compensation were deeply studied through basic salary, total compensation and stock incentives. Studies have shown that company size and company performance are still important factors in determining compensation, which was confirmed in this study once again. In addition, the impact of the characteristics of the directors on compensation has also received some new evidence. Female directors contribute to the company's compensation positively and increasing the proportion of female directors will promote the company's development. However, the proportion of independent directors has reduced the executive compensation, which is contrary to some previous studies. Boards with longer tenure and more work experience may bring positive benefits to the company, so executive compensation could be increased. Finally, the implementation of compensation management law (i.e. say-on-pay laws) does not seem to have a significant impact during 2011-2015. The reason for this may be that the choice of time span is too short, so this result remains to be further studied.